GPU-accelerated 2D sediment transport model for hyper-turbid events in partially mixed estuaries - Sicard, Laure; Garcia-Navarro, Pilar; Martinez-Aranda, Sergio (Jornada de Jóvenes Investigadores del I3A, 2025)
Esturies are coastal environments modelling those environments is very important and requires numerous large scale and time data because of all the different parameters they imply. For this reason, a GPU based model representing the evolution of the water fluxes and sediment and solute fluxes has been tested using data from Guadalquivir estuary located to the southern part of Spain.